Metabolism of Naphthalene, 1-Naphthol, Indene, and Indole by Rhodococcus sp. Strain NCIMB 12038 - Boyd, C. (1997)
The regulation of naphthalene and 1-naphthol metabolism in a Rhodococcus sp. (NCIMB 12038) has been investigated. The microorganism utilizes separate pathways for the degradation of these compounds, and they are regulated independently. Naphthalene metabolism was inducible, but not by salicylate, and 1-naphthol metabolism, although constitutive, was also repressed during growth on salicylate. The biochemistry of naphthalene degradation in this strain was otherwise identical to that found in Pseudomonas putida, with salicylate as a central metabolite and naphthalene initially being oxidized via a naphthalene dioxygenase enzyme to cis-(1R,2S)-1,2-dihydroxy-1,2-dihydronaphthalene (naphthalene cis-diol). A dioxygenase enzyme was not expressed under growth conditions which facilitate 1-naphthol degradation. However, biotransformations with indene as a substrate suggested that a monooxygenase enzyme may be involved in the degradation of this compound. Indole was transformed to indigo by both naphthalene-grown NCIMB 12038 and by cells grown in the absence of an inducer. Therefore, the presence of a naphthalene dioxygenase enzyme activity was not necessary for this reaction. Thus, the biotransformation of indole to indigo may be facilitated by another type of enzyme (possibly a monooxygenase) in this organism.